The challenges of developing a textile-based device for recognizing swallowing movements during different swallowing tasks - Ihalainen, Tiina; Törmä, Saara; Sipilä, Erja; Palovuori, Karri; Vuohijoki, Tiina; Virkki, Johanna (Finnish Journal of eHealth and eWelfare, 2023)
Swallowing difficulty, also known as dysphagia, is a fairly common symptom that may lead to malnutrition, dehydration, pulmonary complications, and a reduced quality of life. Currently, a swallowing evaluation requires a hospital environment, skilled personnel, and expensive devices. Thus, it is important to develop a successful method for evaluating swallowing in an everyday environment. This study developed a textile-based solution that resembles a neck gaiter. Wireless accelerometer and gyroscope sensors embedded inside the gaiter were used to detect swallowing movements. The recognition of swallows was achieved through cervical auscultation and video footage, and this data was subsequently compared with the information obtained from wireless accelerometer and gyroscope sensors. Based on the measurement results for 17 adults without dysphagia, the developed neck gaiter can identify individual swallows of 5 sips of water (with a 97 % identification success rate) and consecutive swallows of 100 ml of water (98 % identification success rate). However, we were not able to recognize swallowing movements from speaking, chewing and head movements. Future research is now needed to develop a prototype to differentiate swallowing movements from other movements, such as chewing and speaking.